THE EFFECT OF LEADERSHIP, WORK EXPERIENCE, COMPENSATION, AND WORK ENVIRONMENT ON WORK PRODUCTIVITY OF PRODUCTION EMPLOYEES - Anti Zalika; Muhammad Rusdi; Fakhrina (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
This study aims to analyze the extent of the influence of leadership, work experience, compensation and work environment on the work productivity of employees in the production. The type of research used in this research is the type of quantitative research. The source of the data comes from the results of a questionnaire aimed at employees of the production division. The population in this study were all employees of the production division, totaling 75 people and the sampling in this study used the saturated sampling method, namely a sampling technique where all members of the population were sampled, this was done because the population was relatively small or less. of 100, with a sample of 75 people. Testing the hypothesis in this study using multiple linear regression, for data analysis with the help of the SPSS Ver 21 program. The results of this study indicate a positive and significant influence between leadership, work experience, compensation and work environment on work productivity, the results of the multiple regression test are Y = 0.470 + 0.079 X1 + 0.975 X2 + 0.067 X3 + 0.060 X4, and the results of the F test are Fcount (636.862) > Ftable (2.50). with a significance value of 0.000 <0.05, it can be concluded that the independent variables namely leadership, work experience, compensation and work environment together have a positive and significant influence on the dependent variable, namely work productivity.